Collaborative Governance in Poverty Alleviation in Rote Ndao Regency, East Nusa Tenggara Province, Indonesia - William Daniel Feoh; Rossy Lambelanova; Meliasta Hapri Tarigan (Sean Institute, 2026)
The high poverty rate in Rote Ndao Regency highlights the need for poverty alleviation efforts that involve multiple stakeholders, as poverty is not only associated with economic factors but is also influenced by education, health, employment opportunities, and limited community resources. This study aims to analyze the implementation of collaborative governance in poverty alleviation in Rote Ndao Regency and to formulate an effective collaboration model to support poverty reduction efforts. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Research informants were selected using purposive sampling techniques and included representatives from local government, the private sector, communities, academics, the media, and the diaspora. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that collaborative governance in poverty alleviation in Rote Ndao Regency has involved various actors; however, its implementation has not yet been optimal. This is reflected in the absence of a structured collaboration forum, weak cross-sectoral coordination, limited resources, and insufficient integration of stakeholder roles. Furthermore, the processes of dialogue, trust-building, shared commitment, and mutual understanding among actors still require strengthening. This study also proposes a collaborative governance model that emphasizes strengthening institutional design, facilitative leadership, and the integrated involvement of multiple stakeholders. Through a more comprehensive and coordinated collaboration model, poverty alleviation programs in Rote Ndao Regency are expected to be implemented more effectively, participatively, and sustainably.